Perbedaan Keterampilan Kolaborasi Siswa pada Materi Sistem Gerak Menggunakan Teams Games Tournament dengan Teams Games Tournament Berbantuan Teka-Teki Silang - Nabila De La Rosa; Harlita; Meti Indrowati (Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan Universitas Mulawarman, 2026)
Collaboration skills are essential competencies in 21st-century biology education, yet classroom practices remain predominantly teacher-centered, limiting student engagement, particularly in complex topics such as the human movement system. This study aimed to examine differences in students’ collaboration skills between the Teams Games Tournament (TGT) model and TGT assisted by Crossword Puzzles (TTS). A quantitative quasi-experimental approach with a pretest–posttest non-equivalent control group design was employed. The participants were eleventh-grade students of SMA Negeri 8 Surakarta in the 2025/2026 academic year, with class XI IPA 1 as the control group and XI IPA 3 as the experimental group. Data were collected using a validated and reliable four-point Likert-scale questionnaire, supported by observation and documentation. Scores were analyzed based on total pretest and posttest results. The Mann–Whitney U test and Cohen’s r were used for data analysis. The results showed no statistically significant difference between groups (p = 0.383), with a small effect size (r = 0.104). These findings indicate that TGT, both with and without crossword puzzle assistance, is equally effective in improving students’ collaboration skills in human movement system learning.